The Effect of Management Support, Compensation, and Work Facilities on Employee Job Satisfaction at PT Gasing Sulawesi in Makassar - Umi Putri; Muh Nur.R; Zalkha Soraya (Yayasan Amerta Insan Unggul, 2026)
In an increasingly competitive business environment, employee job satisfaction is a critical determinant of organizational performance and sustainability, yet many firms still face challenges related to managerial support, compensation fairness, and adequacy of work facilities. This study aimed to examine the effect of management support, compensation, and work facilities on employee job satisfaction at PT Gasing Sulawesi in Makassar. The research employed a quantitative associative design with a population of 50 employees, all of whom were selected using a saturated sampling technique. Primary data were collected through Likert-scale questionnaires and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with SPSS. The results showed that management support (β = 0.206; p = 0.024), compensation (β = 0.362; p < 0.001), and work facilities (β = 0.116; p = 0.033) had positive and significant effects on job satisfaction, both partially and simultaneously. The model explained 66% of the variance in employee job satisfaction (Adjusted R² = 0.660), indicating a substantial explanatory power. Among the predictors, compensation had the strongest influence. These findings suggest that enhancing managerial support, ensuring fair and competitive compensation, and providing adequate work facilities are essential strategies to improve employee job satisfaction. This study contributes to human resource management literature by empirically confirming the combined role of organizational support factors in shaping job satisfaction and offers practical implications for managerial policy development in industrial companies.